Antinuclear antibodies in suspected Systemic lupus erythematosus (SLE) patients of a tertiary care hospital- a retrospective study (Bangladesh Journal of Medical Science, 2022)
Background: In a systemic autoimmune disorder, non-organ-specific autoantibodies binding to the antigens are expressed within the human cells. The presence of antinuclear antibody (ANA) in the blood indicate an autoimmune disease. Objective: The study aims to estimate the frequency and prevalence of ANA in suspected autoimmune disorders in a tertiary care hospital.Materials and methods: A retrospective study and the ANA test results data obtained from the Laboratory Information System and laboratory records.Result: The frequency of the ANA test in six months was 5879; among them, 1638 (27.8 %) had ANA positive test either global or profile with female predominance (2:1). ANA positive test selected for further analysis was 401, in which 154(38%) were from the age group of 20 to 40 years.Conclusion: The estimated prevalence of ANA positive tests was 27.8%, which differed in different sex and age groups. In autoimmune conditions, estimating the prevalence of ANAs influences the trends of antinuclear antibodies. The test frequency and its interpretation assist in patient diagnosis and management, along with specific diagnostic tests.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 279-283